The all-new real estate foreclosure, short-selling, underwater, property auction, positive cash flow book : your ultimate guide to making money in a crashing market - 420663 Howell-Carey, Chantal; Carey, Bill, 1951- (Hoboken, NJ. : Wiley, 2009)
The real estate market has crashed -- Make money investing in a crashing real estate market -- Foreclosures, foreclosures, and foreclosures -- The new foreclosure tactics -- Inside the loss mitigation department -- Your short-sale offer -- Presenting your short-sale offer and closing the transaction -- Buying the mortgage in foreclosure -- Sellers are the new bankers -- Win going in -- No doubt getting out -- Auctioning your property for top dollar -- Types of auctions -- The who, when, and how of your auction -- Buy low and sell lower -- Cash and cash flow is king -- The future of the real estate market.